Diversity and conservation status of Aegla spp. (Anomura, Aeglidae): an update - Santos,Sandro (2017)
Abstract The speciose genus Aegla Leach, 1820 is the only valid extant genus of the anomuran family Aeglidae, bearing 83 known species. This diversity may be even greater since there is some evidence for cryptic speciation. The genus is endemic to southern South America, occurring in freshwater habitats. We assessed the conservation status of 82 species of Aegla and found almost 70% of them under some level of threat, which represents a concerning proportion. Major threats to the group include freshwater pollution with urban, agricultural and industrial effluents, habitat modification and fragmentation, riparian forest removal, among others. Conservation measures are required to mitigate the major threats to freshwater ecosystems along rivers where the group occurs.